Factors Influencing Fertility Intentions Among Working and Non-Working Women in Bangladesh - Sarkar, Bidduth Kumar; Md. Asadujjaman; Barman, Sourav Kumar; Biswas , Bristi; Sarmistha Paul Setu; Roy, Matrika Saha (Ethiopian Journal of Reproductive Health, 2025)
Our study aimed to examine the desire for having more children and its determinants among childbearing women in Bangladesh due to dearth of sufficient data of this region. Here a secondary data analysis was done on 2017 Bangladesh Demographic and Health Survey/BDHS. A total of 20,127 fertile, married, and sexually active women were included this study. Multilevel mixed-effect logistic regression model was done to show association between fertility desire and explanatory variables. In Bangladesh, 26.5% of working and non-working women expressed a wish for more children. It was discovered that women between the ages of 15 and 24 (66.6%), the richest women (29.6%), women with higher education levels (46.6%), urban residents (27.4%), women who had their first cohabitation at the age of ?25 (42.8%), women who used contraceptives (32.8%), and women who had at most two ideal children had higher intention of being fertile (27.1%). Compared to women with 1-2 children (41.2%) or 3+ children (24.4%), those with a greater number of living children showed significantly higher intention (80%). Compared to those whose spouses were less educated or worked in agriculture, women whose husbands held non-agricultural jobs (29.6%) or higher education (36.1%) expressed greater intention of having child. We found that the overall desire for having more children among Bangladeshi women was influenced significantly by socio-economic and demographic characteristics such as age, education, wealth, age at first cohabitation, contraceptive use and many more. Specific public health interventions on fertility rate control existant in Bangladesh ought to critically count these factors.